Pengaruh Kompetensi Dosen Terhadap Kinerja Dosen Di Universitas Trunojoyo Madura - Aththaariq Aththaariq; R.M. Mochammad Wispandono; M. Alkirom Wildan (Trunojoyo University of Madura, 2014)
This study is aimed to analyze the influence of pedagogical competence (X1), professional competence (X2), social competence (X3), and personality competence (X4) to the dependent variable, the performance of the lecturers in Trunojoyo Madura University. The data used in this study are primary data. The data are collected from the result of spreading the questioner out, while the respondents of this study are the lecturers in Trunojoyo Madura University who have been certified as active starting from 2008 until 2011. The respondents are 78 lecturers. The technique of taking the sample is by using judgemental sampling which uses the analysis method of double linier regression. The result shown that pedagogical competence (X1), professional competence (X2), social competence (X3), and personality competence (X4) affected significantly to the lecturer’s performance, either simultaneously or partially. The coefficient of double determination (R2) shows the number of 0,796 which means 79,6% of lecturer’s performance is influenced by the change of all independent variables, and the rest is 20,4% which influenced by the variable which while the variable who has dominance influence is pedagogic competence variabel with significance value about 0.000 and has beta value about 0.426.